A surface-deposited supported germanium-based or titanium-germanium-based catalyst and its preparation method and use

The surface-deposited supported germanium-based or titanium-germanium-based catalysts address hue and deposition issues in PETG and PCTG polymerization, enhancing catalytic efficiency and product quality while reducing germanium use and device fouling.

CN118085259BActive Publication Date: 2024-12-20JIANGSU GUOWANG HIGH TECH FIBER CO LTD +1
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202410166675.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-02-06
Publication Date
2024-12-20
Estimated Expiration
2044-02-06

AI Technical Summary

Technical Problem

Existing catalysts for PETG and PCTG polymerization, such as antimony, titanium, and tin-based catalysts, suffer from issues like poor hue, yellowing, toxicity, and environmental pollution, while germanium dioxide catalysts face challenges with large particle sizes and deposition in polymerization devices, leading to incomplete reactions and device fouling.

Method used

A surface-deposited supported germanium-based or titanium-germanium-based catalyst is prepared by forming a load deposition layer on an inorganic porous carrier through coprecipitation of metal salts, followed by hydrolysis and reaction with germanium or titanium sources to create a catalyst with a larger specific surface area and porous structure, allowing for efficient catalytic activity in a suspended state.

Benefits of technology

The new catalysts improve viscosity and hue qualities of PETG and PCTG products, enhance catalytic efficiency by 15-20%, reduce germanium usage, and prevent deposition in polymerization devices, offering better thermal stability and cost-effectiveness.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The present invention relates to a surface-deposited supported germanium-based or titanium-germanium-based catalyst and its preparation method and use. The catalyst includes a carrier, a supported deposit layer and an active component, and the preparation method includes the following steps: a suspension of the carrier, a water-soluble calcium salt, a water-soluble aluminum salt, a water-soluble zirconium salt, a water-soluble hydroxide, and an alkali are subjected to precipitation reaction, filtration, and calcination to form a supported deposit layer on the carrier; this step increases the specific surface area of ​​the carrier, and the supported deposit layer has a strong chemical anchoring effect on the active component; a suspension of the carrier containing the supported deposit layer is subjected to hydrolysis reaction with a germanium source or a germanium source and a titanium source to obtain a catalyst precursor; the precursor is reacted with a silicate and water, and an active component is loaded on the supported deposit layer to obtain a catalyst. When used to catalyze the polymerization of PETG or PCTG, the viscosity and the quality of each hue can be significantly improved, and the catalyst has good thermal stability, participates in the polymerization reaction in a suspended state, and will not be deposited in the polymerization device system.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a surface deposited supported germanium-based or titanium-germanium-based catalyst and a preparation method and application thereof. Background Art

[0002] PETG and PCTG are both transparent, non-crystalline copolyesters. Both can be prepared by esterification and polymerization of terephthalic acid PTA, ethylene glycol EG, and 1,4-cyclohexanedimethanol CHDM in the presence of an esterification catalyst and a polymerization catalyst. The two can be distinguished according to the different molar proportions of the segments corresponding to CHDM in the total diol (CHDM and EG) segments in the copolyester. Generally, the polymerization product with a molar proportion of 31% to 32% of the segments corresponding to CHDM is called PETG copolyester; and the polymerization product with a molar proportion of 60% to 62% of the segments corresponding to CHDM is called PCTG. Both polymerization products have high transparency, good toughness and impact strength, excellent low-temperature toughness, high tear resistance, good processing performance, and excellent chemical resistance. Both can be processed by traditional extrusion, injection molding, blow molding, and blister molding. Both can be widely used in the market of plates and sheets, high-performance shrink films, bottles, and profiles; they can also be used to produce toys, household utensils, and medical supplies.

[0003] The catalysts used to catalyze the esterification and polymerization of PETG and PCTG generally include antimony catalysts, titanium catalysts, germanium catalysts, tin catalysts, etc. When catalyzing the synthesis of PETG and PCTG, the brightness and non-crystalline properties of the polymer product are crucial.

[0004] Antimony-based catalysts are the cheapest and have good catalytic polymerization activity. However, they are prone to reduction reactions to generate antimony ash during high-temperature reactions, which can cause the hue L value of PETG and PCTG polymer products to be very low (generally ≤56.0) and the b value to be high (generally ≥4.0), resulting in poor product appearance hue. The L value of the product cannot be improved by colorants, so antimony-based catalysts are usually not used alone during polymerization.

[0005] Titanium-based catalysts are highly active, but they also catalyze high levels of side reactions, resulting in more by-products in the product, a yellowish hue, and a high b value. Even with the use of colorants for adjustment, the product hue is very poor, so titanium-based catalysts are usually not used alone during polymerization.

[0006] Tin-based catalysts also have problems with poor sunlight fastness and yellowing of slices. In addition, tin catalysts are toxic and cause serious environmental pollution.

[0007] Germanium catalysts are the most commonly used catalysts for the synthesis of PETG and PCTG. They are usually used alone or in combination with other catalysts. They have a mild catalytic effect, low level of side reactions, and good hue for polymer products, usually with an L value of ≥63.5 and a b value of ≤1.0.

[0008] Germanium dioxide is the most commonly used germanium-based catalyst. Although it has the aforementioned advantages, it has a very high hardness and it is usually difficult to crush the germanium dioxide powder to a particle size below 0.1-0.3um required for solid-phase catalysts. The particle size of commercially available germanium dioxide powder is usually ≤75μm. This particle size is too large. If the germanium dioxide powder is added in the late stage of esterification of the self-polymerization system, the polymerization reaction cannot be completed due to poor catalytic effect.

[0009] The existing method of using germanium dioxide is to add germanium dioxide powder to distilled water under stirring conditions and reflux for a long time, so that germanium dioxide reacts with water to form germanic acid (H2GeO3 or Ge(OH)4), and the general configuration concentration is only about 1.0%. And germanium dioxide crystals include three types: hexagonal, tetragonal and amorphous, among which only the tetragonal is slightly soluble in water, and the other two are difficult to dissolve. In addition, the specific gravity of the hexagonal crystal is 4.228, and the specific gravity of the tetragonal crystal is 6.239. Even if it is added to the polymerization system in the form of the aforementioned germanic acid, it is easy to dehydrate and return to the solid phase of germanium dioxide under the high temperature conditions of the esterification and polymerization stages. After a long time, it will be deposited on the wall of the reactor and the melt pipe, affecting the long-term operation of the device.

[0010] Chinese patent CN104640905A discloses using titanium compounds and germanium compounds as composite catalysts for catalyzing PCTG. Although the hue of the product can be improved, the hue performance of the product still needs to be improved.

[0011] Chinese patent CN113429549B discloses a composite catalyst for catalyzing the polymerization of polycyclohexylene dimethylene terephthalate, wherein the catalyst is a metal / non-metal composite, which is a first catalyst Zr-Te-P, a second catalyst Si-Zr-B or a third catalyst Si-Zr-Sn-Ba. Although the composite catalyst can increase the polymerization reaction rate and reduce the occurrence of side reactions, the hue performance of the product still needs to be improved.

[0012] Chinese patent CN116693830B discloses a quaternary ammonium titanium / zirconium chelate catalyst prepared by reacting 2,3-dihydroxypropyl-trimethylammonium chloride with tetrabutyl titanate or tetrabutyl zirconate, which is used to catalyze the copolymerization of modified PETG. Although the color of the copolyester product is good, the structure of the catalyst is relatively complex and the preparation process is relatively complicated.

[0013] Chinese patent CN1121727A discloses a composite catalyst of manganese diacetate, zinc acetate, isopropoxy titanium and germanium dioxide, but the viscosity of PETG prepared by the composite catalyst is not high enough. Summary of the invention

[0014] The purpose of the present invention is to provide a method for preparing a surface-deposited supported germanium-based or titanium-germanium-based catalyst. When the germanium-based or titanium-germanium-based catalyst obtained by the preparation method is used to catalyze the polymerization of PETG or PCTG, the viscosity and various hue qualities of the product can be significantly improved, and the catalyst has good thermal stability, participates in the polymerization reaction in a suspended state, and will not be deposited in the polymerization device system.

[0015] In order to achieve the above object, the technical solution adopted by the present invention is:

[0016] The invention discloses a method for preparing a supported catalyst, wherein the supported catalyst is a surface-deposited supported germanium-based catalyst, the catalyst comprises a carrier, a supported deposited layer and an active component, the carrier is an inorganic porous material coated and modified by silicate, the supported deposited layer is located on the carrier and has a porous structure, and the active component is deposited on the supported deposited layer. The preparation method comprises the following steps: subjecting a suspension of the carrier, a water-soluble calcium salt, a water-soluble aluminum salt, a water-soluble zirconium salt, a water-soluble hydroxide and an alkali to precipitation reaction, filtering and heating treatment to form the supported deposited layer on the carrier; the alkali is selected from carbonate and / or bicarbonate; the specific surface area of ​​the carrier containing the supported deposited layer is greater than the specific surface area of ​​the carrier; dispersing the carrier containing the supported deposited layer in water to obtain a suspension of the carrier containing the supported deposited layer; subjecting the suspension of the carrier containing the supported deposited layer to hydrolysis reaction with a germanium source to obtain a catalyst precursor; reacting the catalyst precursor with silicate and water to load the active component on the supported deposited layer to obtain the surface-deposited supported germanium-based catalyst.

[0017] Another technical solution adopted by the present invention is:

[0018] The invention discloses a method for preparing a supported catalyst, wherein the supported catalyst is a surface-deposited supported titanium-germanium-based catalyst, the catalyst comprises a carrier, a supported deposition layer and an active component, the carrier is an inorganic porous material coated and modified by silicate, the supported deposition layer is located on the carrier and has a porous structure, and the active component is deposited on the supported deposition layer. The preparation method comprises the following steps: subjecting a suspension of the carrier, a water-soluble calcium salt, a water-soluble aluminum salt, a water-soluble zirconium salt, a water-soluble hydroxide and a base to precipitation reaction, filtering and calcining, so as to form the supported deposition layer on the carrier; the base is selected from carbonate and / or bicarbonate; the specific surface area of ​​the carrier containing the supported deposition layer is greater than the specific surface area of ​​the carrier; dispersing the carrier containing the supported deposition layer in water to obtain a suspension of the carrier containing the supported deposition layer; subjecting the suspension of the carrier containing the supported deposition layer to hydrolysis reaction with a germanium source and a titanium source to obtain a catalyst precursor; reacting the catalyst precursor with silicate and water, and loading the active component on the supported deposition layer to obtain the surface-deposited supported titanium-germanium-based catalyst.

[0019] The present invention first prepares a load deposition layer on the carrier through a coprecipitation reaction of metal salts such as calcium, aluminum, and zirconium on the carrier. The load deposition layer is a basic carbonate of three metals and provides a load deposition site for the active component. The basic carbonate decomposes carbon dioxide gas after calcination, so that the load deposition layer has a porous structure, and the specific surface area of ​​the layer is greater than the specific surface area of ​​the carrier. That is, the present invention precipitates the load deposition layer on the carrier, thereby expanding the specific surface area of ​​the carrier, and at the same time making the carrier have more microporous structures, which is more conducive to the effective loading of the active component. Among them, the zirconium element in the load deposition layer can increase the strength of the carrier, and the calcium element and the aluminum element are conducive to forming the porous structure of the load deposition layer.

[0020] When preparing a germanium-based catalyst, when loading the active component through an in-situ hydrolysis reaction, the germanium source undergoes a hydrolysis reaction on the loaded deposition layer to form germanium dioxide, which serves as a catalyst precursor. The catalyst precursor reacts with silicate and water, and the catalyst precursor germanium dioxide is hydrolyzed to form a germanium-hydroxy structure, and the silicate is hydrolyzed to form a silicon hydroxide containing a hydroxyl group. The two will form a structure containing a Ge-O-Si bond through a condensation reaction, and the structure contains germanium elements and serves as an active component of the catalyst.

[0021] When preparing titanium-germanium based catalysts, the raw materials for the hydrolysis reaction contain a titanium source in addition to a germanium source. The titanium source will also be hydrolyzed first to form titanium tetrahydroxide. The titanium tetrahydroxide and the silicon hydroxide containing hydroxyl groups will undergo a condensation reaction to generate a compound containing a Ti-O-Si bond. The compound contains titanium element, which also serves as an active component of the catalyst. At this time, the active components of the catalyst include germanium element and titanium element, which is a composite catalyst of titanium and germanium.

[0022] The present invention forms a load deposition layer with a larger specific surface area and a porous structure on a carrier first, so that the active component (single germanium element or a composite component of titanium element and germanium element) can participate in the catalytic reaction with a nanoparticle size, thereby improving the activity of the catalytic polymerization reaction, inhibiting the occurrence of side reactions, and improving the hue of the copolyester product.

[0023] In some embodiments, the inorganic porous material is selected from a combination of one or more of nanoporous alumina, nanoporous alumina-zirconia, nanoporous silica and nanoporous barium sulfate, and has a particle size of 20 to 80 nm, preferably 25 to 60 nm, more preferably 30 to 45 nm, and a specific surface area of ​​220 to 400 m 2 / g, preferably 230-320m 2 / g.

[0024] In some embodiments, the water-soluble calcium salt, water-soluble aluminum salt, and water-soluble zirconium salt of the carrier-loaded deposition layer are respectively selected from sulfates, acetates, or chlorides of the corresponding metal elements; and / or, the water-soluble hydroxide is selected from one or both of sodium hydroxide and potassium hydroxide.

[0025] In some embodiments, the carbonate is selected from a combination of one or more of sodium carbonate, potassium carbonate and ammonium carbonate.

[0026] In some embodiments, the bicarbonate is selected from a combination of one or more of sodium bicarbonate, potassium bicarbonate and ammonium bicarbonate.

[0027] In some embodiments, the molar ratio of the water-soluble calcium salt, the water-soluble aluminum salt, and the water-soluble zirconium salt for preparing the carrier-loaded deposition layer is 0.5-2.5: 1.0-2.0: 0.8-3.5.

[0028] In some embodiments, the water-soluble calcium salt, water-soluble aluminum salt, and water-soluble zirconium salt are added dropwise to the suspension of the carrier in the form of aqueous solutions; the water-soluble hydroxide and alkali are added dropwise to the suspension of the carrier in the form of aqueous solutions; and the preparation method controls the simultaneous addition of the two.

[0029] In some embodiments, the molar concentration of the water-soluble calcium salt in the aqueous solution is 0.1 to 3.0 mol / L.

[0030] In some embodiments, the molar concentration of the water-soluble aluminum salt in the aqueous solution is 0.5 to 2.5 mol / L.

[0031] In some embodiments, the molar concentration of the water-soluble zirconium salt in the aqueous solution is 0.1 to 3.5 mol / L.

[0032] In some embodiments, the total molar concentration of the water-soluble hydroxide and the base in the aqueous solution is 0.1 to 2.0 mol / L.

[0033] In some embodiments, when forming the supported deposition layer on the support, the precipitation reaction is performed at a pH of 10-12.

[0034] In some embodiments, the precipitation reaction time is 8-11 hours.

[0035] In some embodiments, the precipitation reaction temperature is 70-100°C.

[0036] In some embodiments, the preparation method further includes the steps of continuing to stir the suspension for 1.0-4 hours after the precipitation reaction is completed, then pressurizing it to 0.7-1.2 MPa, stirring and heating it to 180-200°C, balancing it for 2-4 hours, then rapidly releasing the pressure to normal pressure, cooling the suspension to room temperature, filtering, washing, drying, and crushing.

[0037] In some embodiments, the preparation method further comprises a step of making pores in the carrier after the precipitation reaction and before filtration; preferably, the step of making pores in the carrier comprises the steps of pressurizing and heating the reaction system after the precipitation reaction and decompressing it to normal pressure.

[0038] In some embodiments, the pressurized pressure is 0.7-1.2 MPa.

[0039] In some embodiments, the heating is performed to a temperature of 180-200° C., which serves to decompose the carbonate hydroxide generated by the precipitation reaction, thereby increasing the specific surface area of ​​the carrier.

[0040] In some embodiments, when the supported deposition layer is formed on the carrier, the temperature of the heat treatment is 290-310°C.

[0041] In some embodiments, the heating treatment time is 2-6 hours.

[0042] In some embodiments, the supported deposited layer is further dehydrated and made porous, and the specific surface area of ​​the supported powder containing the supported deposited layer after treatment is 600 to 900 m 2 / g, and the powder particle size is 20-50nm, and a large number of nanopores are formed on the powder surface.

[0043] In some embodiments, a carrier powder containing a loaded deposition layer is mixed with water under stirring conditions to form a suspension with a mass concentration of 10%-20%, and then ground by an ultrafine grinder for 2-3 times, and the ground suspension is heated to 60-90°C; a certain amount of germanium tetrachloride or tetraethyl germanium is slowly added to the suspension within 4.0-6.0 hours, and the germanium tetrachloride or tetraethyl germanium reacts with water under stirring conditions to hydrolyze into germanium dioxide and deposit on the surface of the loaded deposition layer. After the addition is completed, stirring and aging are continued at 80-90°C for 1.5-2.0 hours, and then a certain amount of silicate is slowly added within 2.0-4.0 hours for surface coating. After the addition is completed, aging is continued for 1.0-3.0 hours to complete the preparation of the surface-deposited loaded germanium-based catalyst, and then filtered, washed, dried, and crushed to prepare the surface-deposited loaded germanium-based catalyst.

[0044] In some embodiments, the germanium source is selected from one or both of germanium tetrachloride and tetraethylgermanium.

[0045] In some embodiments, the silicate is selected from a combination of one or more of tetraethyl silicate, tetrabutyl silicate, and tetrapropyl silicate.

[0046] In some embodiments, the germanium source is added dropwise to the suspension of the support containing the supported deposition layer to perform a hydrolysis reaction.

[0047] In some embodiments, the mass ratio of the silicate to the germanium source is 1:0.2-0.5.

[0048] In some embodiments, in the surface-deposited supported germanium-based catalyst, the mass ratio of the support, supported deposited layer, and effective germanium in the active component is 72.5-87.5:7.5-12.5:5.0-15.0. In the present invention, the effective germanium in the active component refers to the germanium element in the active component calculated by converting it into germanium dioxide in an equimolar manner.

[0049] In some embodiments, the preparation method further includes preparing a surface-deposited supported germanium-based catalyst in ethylene glycol under stirring conditions to form a suspension with a mass concentration of 10%-20%, stirring evenly, and then grinding and filtering to prepare a catalyst suspension. The catalyst suspension has an effective germanium element content (as germanium dioxide) of 1.0% to 3.0%, and is a stable suspension that can be stored for 3.0 to 5.0 months without sedimentation.

[0050] In some embodiments, the carrier powder containing the load deposition layer is mixed with distilled water under stirring conditions to prepare a suspension with a mass concentration of 10%-20%, and then ground by an ultrafine grinder for 2-3 times, and the ground suspension is heated to 60-90° C.; under stirring conditions, a certain amount of germanium tetrachloride or tetraethyl germanium and tetrabutyl titanate or isopropyl titanate is simultaneously added to the above suspension within 6.0-8.0 hours, and sodium hydroxide-sodium bicarbonate solution is simultaneously added, and the pH value of the system is maintained between 10 and 12 during the addition process. , a hydrolysis co-precipitation reaction is carried out to deposit the titanium source and the germanium source on the surface of the nanoporous supported deposition layer at the same time. After the dropwise addition is completed, the mixture is aged for 1.0 to 2.0 hours under stirring conditions; a certain amount of silicate is slowly dropped into the mixed solution to adjust the pH value of the system to between 9 and 10. After the dropwise addition is completed, the mixture is aged for 1.0 to 3.0 hours to coat the surface of the nano-supported catalyst, and then the suspension is filtered, and the filter cake is washed with water, and the washing is repeated until the chloride ions are completely removed; the filter cake is dried and crushed to prepare a surface-deposited supported titanium-germanium-based catalyst.

[0051] For germanium-based catalysts, in some embodiments, the preparation method further includes the steps of filtering, washing, and drying after loading the active components on the loaded deposition layer, and the loaded catalyst is in a powder state; preferably, the effective germanium content in the powdered loaded catalyst is 5.0% to 15.0%.

[0052] For titanium-germanium based catalysts, in some embodiments, the preparation method further includes the steps of filtering, washing, and drying after loading the active components on the loaded deposition layer, and the loaded catalyst is in a powder state; preferably, in the loaded catalyst in a powder state, the effective germanium content is 2.5% to 7.5%, and the effective titanium content is 0.6% to 1.9%.

[0053] In some embodiments, the germanium source is selected from one or both of germanium tetrachloride and tetraethylgermanium.

[0054] In some embodiments, the titanium source is selected from a combination of one or more of tetraisopropyl titanate, tetrabutyl titanate and titanium tetrachloride.

[0055] In some embodiments, the silicate is selected from a combination of one or more of tetraethyl silicate, tetrabutyl silicate, and tetrapropyl silicate.

[0056] In some embodiments, a hydrochloric acid solution of a germanium source and a titanium source are added dropwise to the suspension of the support containing the supported deposition layer to perform a hydrolysis reaction.

[0057] In some embodiments, the ratio of the mass of the silicate to the total mass of the germanium source and the titanium source is 1:0.2-0.5.

[0058] For titanium-germanium catalyst, in some embodiments, in the surface-deposited supported titanium-germanium-based catalyst, the mass ratio of the support, supported deposited layer, effective germanium in the active component, and effective titanium is 78.1-89.4: 7.5-12.5: 2.5-7.5 (in terms of germanium dioxide): 0.6-1.9 (in terms of titanium dioxide). In the present invention, effective titanium refers to the titanium element in the active component calculated by converting it into titanium dioxide in an equimolar manner.

[0059] In some embodiments, the molar ratio of titanium element to germanium element in the active component is 1:1.5 to 4.5.

[0060] In some embodiments, the preparation method also includes preparing a surface-deposited loaded titanium-germanium-based catalyst into a suspension with a mass concentration of 10%-20% in ethylene glycol under stirring conditions, stirring evenly, and then grinding and filtering to prepare a catalyst suspension. The catalyst suspension has an effective germanium element content (calculated as germanium dioxide) of 0.5% to 1.5%, and an effective titanium element content (calculated as titanium dioxide) of 0.12% to 0.38%. It is a stable suspension that can be stored for 3.0 to 5.0 months without sedimentation.

[0061] For germanium-based catalysts, in some embodiments, the preparation method further includes the steps of filtering, washing, and adding a mixed solvent of water and ethylene glycol to disperse after loading the active component on the loaded deposition layer, and the loaded catalyst is in a suspension state.

[0062] For titanium-germanium based catalysts, in some embodiments, the preparation method further comprises the steps of filtering, washing, and adding a mixed solvent of water and ethylene glycol to disperse after loading the active components on the loaded deposition layer, and the loaded catalyst is in a suspension state.

[0063] In some embodiments, the particle size of the supported germanium-based catalyst and the titanium-germanium-based composite catalyst is 60-150 nm; and the specific surface area is 100-280 m 2 / g, the catalyst particle size is between nanometers and sub-nanometers, and the catalytic active centers on the catalyst particle surface can fully contact with the oligomers in a nanometer state, thereby improving the efficiency of the polymerization catalytic reaction.

[0064] The present invention also provides a supported catalyst prepared by the preparation method of the supported catalyst. The corresponding supported catalyst is a germanium-based catalyst or a titanium-germanium-based catalyst. When these two types of catalysts are used to catalyze the polymerization of PETG or PCTG, the viscosity and various hue qualities of the product can be significantly improved, and the thermal stability is good. The catalyst participates in the polymerization reaction in a suspended state and will not be deposited in the polymerization device system.

[0065] The present invention also provides the use of the above-mentioned germanium-based catalyst or titanium-germanium-based catalyst for catalyzing polyester synthesis.

[0066] In some embodiments, during the synthesis of polyester, a germanium-based catalyst or a titanium-germanium-based catalyst is used alone, or a germanium-based catalyst or a titanium-germanium-based catalyst is used together with other catalysts such as a titanium-based catalyst.

[0067] In some embodiments, the polyester is selected from PETG or PCTG.

[0068] In the present invention, PETG refers to a copolyester of terephthalic acid PTA, ethylene glycol EG, and 1,4-cyclohexanedimethanol CHDM, and in the copolyester, the segment corresponding to CHDM accounts for 31% to 32% by mole in the total diol (CHDM and EG) segment; PCTG refers to a copolyester of terephthalic acid PTA, ethylene glycol EG, and 1,4-cyclohexanedimethanol CHDM, and in the copolyester, the segment corresponding to CHDM accounts for 60% to 62% by mole in the total diol (CHDM and EG) segment.

[0069] Due to the application of the above technical solution, the present invention has the following advantages compared with the prior art:

[0070] When the surface-deposited nano-supported germanium-based or titanium-germanium-based catalyst of the present invention is used to catalyze the synthesis of PETG or PCTG polyester, the in-situ deposited germanium element or the composite element of germanium element and titanium element has a larger specific surface area, and can obtain better catalytic activity and reaction efficiency. The catalyst maintains a stable nano-powder state during the esterification and polymerization processes, and can catalyze the polymerization reaction more efficiently. Compared with traditional solid-phase germanium dioxide, the catalytic efficiency can be increased by 15% to 20%, and the product quality can be greatly improved, and the product color is significantly improved.

[0071] The two types of catalysts of the present invention have higher catalytic efficiency. When achieving the same catalytic effect, the usage of germanium can be significantly reduced. However, germanium is expensive, which can further reduce the cost of the catalyst.

[0072] The two types of catalysts of the present invention can form a stable suspension in ethylene glycol, and the specific gravity of the catalyst powder is about 1.0 to 1.1, which is much smaller than the specific gravity of germanium dioxide (above 4.0). The catalyst of the present invention has good dispersion stability in ethylene glycol and can be suspended in the polymerization system during polymerization. DETAILED DESCRIPTION

[0073] The above scheme is further described below in conjunction with specific examples; it should be understood that these examples are used to illustrate the basic principles, main features and advantages of the present invention, and the present invention is not limited to the scope of the following examples; the implementation conditions used in the examples can be further adjusted according to specific requirements, and the unspecified implementation conditions are usually the conditions in conventional experiments. Unless otherwise specified in the following examples, all raw materials are purchased from commercial sources or prepared by conventional methods in the art.

[0074] The above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with the technology to understand the content of the present invention and implement it accordingly, and they cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.

[0075] Example 1

[0076] This embodiment provides a supported germanium-based catalyst, and uses it in the polymerization of PETG or PCTG, and the specific steps are as follows:

[0077] Preparation of catalyst:

[0078] 1) Ethylene glycol is heated to 50° C., and accurately measured barium hydroxide octahydrate is slowly added into the reactor under high-speed stirring conditions (high-speed homogenizer: speed: 3000-6000 rpm), stirred until completely dissolved, and then 10% mass concentration of dilute sulfuric acid is quickly added into the reactor according to the molar ratio of barium ions, and kept stirring at high speed for 1.0 hour. The reaction heat causes the suspension to be heated to about 90° C., and the pH of the suspension is adjusted to be stable at 7.0, and then the temperature is raised to reflux, and the water is evaporated, and the temperature is lowered to 170° C., and ethylene glycol is added to make the mass content of barium sulfate powder 20%, and then stirred for 0.5 hour, and the pH value is measured again until the pH value of the suspension is completely stable at 7.0. The particle size of the obtained barium sulfate powder is 20 nm, and the specific surface area is 350 m 2 / g.

[0079] 2) Tetraethyl silicate and sodium hydroxide are added dropwise to the ethylene glycol suspension of barium sulfate with a pH value of 7.0, so that the surface of the barium sulfate powder is coated with a silicon dioxide layer; after aging for 6 hours, the prepared mixed aqueous solution of calcium chloride, aluminum chloride, and zirconium acetate (wherein the molar concentration of calcium chloride is 2.5 mol / L, the molar concentration of aluminum chloride is 0.5 mol / L, and the molar concentration of zirconium acetate is 0.8 mol / L) and the mixed aqueous solution of sodium hydroxide and sodium bicarbonate with a total molar concentration of 0.5 mol / L are added dropwise to the reactor at the same time under high-speed stirring conditions, according to the total valence of the above three metal ions being equal to the total valence of hydroxide and carbonate ions, and the pH value of the suspension is strictly controlled to be between 10.0 and 10.2 during the dropping process. The dropping time is controlled to be 11 hours, and the reaction temperature is controlled to be 80°C, so that the above three metals are deposited on the surface of the carrier. The obtained suspension was stirred for 1.0 hour, then stirred under pressure (pressure of 0.7 MPa), and heated to 180°C at the same time. After balancing for 2.0 hours, the pressure was quickly released to normal pressure, and the suspension was cooled to room temperature, filtered, washed, dried, and crushed by an ultrafine grinder. It was then placed in a muffle furnace for calcination at a temperature of 290°C for 6 hours. The metal basic carbonate deposited on the surface of the carrier was dehydrated and made porous, so that a load deposition layer with a porous structure was formed on the surface of the carrier. The specific surface area of ​​the carrier containing the load deposition layer is 600 to 900 m 2 / g.

[0080] 3) Add distilled water to the carrier containing the load deposition layer obtained in step 2) under stirring conditions to prepare a suspension with a mass percentage of 20%. After grinding the suspension twice with an ultrafine grinder, the suspension is heated to 90°C. A certain amount of germanium tetrachloride is slowly added dropwise to the above suspension under stirring conditions within 4.0 hours. The germanium tetrachloride reacts with water to hydrolyze to generate germanium dioxide, which is deposited on the surface of the load deposition layer. After the addition is completed, the suspension is stirred and aged for 1.5 hours at 90°C, and then a certain amount of silicate is slowly added to the suspension within 2.0 hours. After the addition is completed, the suspension is aged for 1.0 hour to obtain a suspension of the catalyst. The mass ratio of silicate to germanium tetrachloride is 1:0.2.

[0081] 4) The catalyst suspension is filtered, washed with distilled water, dried and crushed to obtain a supported germanium-based catalyst powder, which can be directly packaged and stored. When used for polymerization, the powder is dispersed in ethylene glycol to obtain a suspension, in which the mass percentage of the catalyst powder is 20%. The specific surface area of ​​the catalyst powder is 280 m 2 / g, and the particle size is 100nm. In the catalyst powder, the mass ratio of effective germanium in the carrier, the load deposition layer and the active component is 72.5:7.5:5.0.

[0082] PETG polymerization:

[0083] Continuous polymerization is carried out on a 30,000 tons / year PETG continuous polymerization device, which includes an esterification kettle, a second esterification kettle (three-chamber structure), a prepolymerization kettle, a second prepolymerization kettle, and a high-viscosity final polymerization kettle.

[0084] First, pure terephthalic acid (PTA), ethylene glycol (EG) and molten 1,4-cyclohexanedimethanol (CHDM) are accurately measured for slurry preparation, and the prepared catalyst suspension is injected into the slurry delivery pipeline. Liquid, as an esterification catalyst, its total mass dosage of the melt: 10ppm (in terms of germanium dioxide), the prepared slurry is transported to the esterification kettle one through a screw metering pump, the temperature in the esterification kettle one is controlled at 254-255°C, the process tower pressure is 70-80kpa (positive pressure), the esterification kettle two is a multi-chamber design with three sub-chambers, which is convenient for adding various additives, the above-prepared catalyst suspension is added to the second chamber of the esterification kettle two, as a polymerization catalyst, the polymerization catalyst accounts for 60ppm of the total mass dosage of the melt (in terms of germanium dioxide), and the coloring is added to the esterification chamber three The esterification kettle is a normal pressure reactor, and the esterification temperatures of the three chambers are controlled as follows: 255-256°C for chamber 1, 253-254°C for chamber 2, and 257-258°C for chamber 3; the esterified materials after the esterification reaction are introduced into the prepolymerization kettle, which is a vertical stirring structure with an inner and outer chamber design, and the reaction temperature of the prepolymerization kettle is controlled at 258-260°C and the vacuum degree is 9.0-11.0Kpa. The oligomers polymerized in the prepolymerization kettle are introduced into the prepolymerization kettle 2, which is a single-axis horizontal disc reactor. The reaction temperature of the reactor is 260-262°C. The prepolymer after the reaction of the second prepolymerization reactor is introduced into the high-viscosity final polymerization reactor through the prepolymer melt pump and the prepolymer filter. The high-viscosity final polymerization reactor is a front and rear double-axis horizontal disc reactor. The reactor outlet temperature is controlled at 265-268°C, the vacuum degree is 90-110 Pa, the outlet melt dynamic viscosity is controlled at 635-650 Pa.s, and the outlet PETG characteristic viscosity is controlled at 0.781 (measured in a mixed solvent with a volume ratio of phenol: tetrachloroethane of 3:2). The PETG slice indicators are shown in Table 1.

[0085] Or PCTG polymerization:

[0086] Continuous polymerization is carried out on a 30,000 ton / year PCTG continuous polymerization unit, which includes an esterification kettle, a second esterification kettle (three-chamber structure), a prepolymerization kettle, a second prepolymerization kettle, and a high-viscosity final polymerization kettle.

[0087] First, pure terephthalic acid (PTA), ethylene glycol (EG) and molten 1,4-cyclohexanedimethanol (CHDM) are accurately measured for slurry preparation, and the prepared catalyst suspension is injected into the slurry delivery pipeline as an esterification catalyst. , which accounts for 10ppm (in terms of germanium dioxide) of the total mass of the melt. The prepared slurry is transported to the first esterification kettle through a screw metering pump. The temperature in the first esterification kettle is controlled at 256-257°C. The process tower pressure is 70-80kpa (positive pressure). The second esterification kettle is a multi-chamber design with three sub-chambers, which is convenient for adding various additives. The above-prepared catalyst suspension is added to the second chamber of the second esterification kettle as a polymerization catalyst. The polymerization catalyst accounts for 60ppm (in terms of germanium dioxide) of the total mass of the melt. Toner and stabilizer are added to the third esterification chamber. The esterification kettle is a normal pressure reactor, and the esterification temperatures of the three chambers are controlled as follows: 255-256°C for chamber 1, 253-254°C for chamber 2, and 260-262°C for chamber 3; the esterified materials after the esterification reaction are introduced into the prepolymerization kettle, which is a vertical stirring structure with inner and outer chamber designs, and the reaction temperature of the prepolymerization kettle is controlled at 266-268°C and the vacuum degree is 9.0Kpa; the oligomers polymerized in the prepolymerization kettle are introduced into the prepolymerization kettle, which is a single-axis horizontal disc reactor, and the reaction temperature of the prepolymerization kettle is controlled at 266-268°C and the vacuum degree is 9.0Kpa. The temperature of the reactor is controlled at 272-274°C. The prepolymer after the reaction in the second prepolymerization reactor is introduced into the high-viscosity final polymerization reactor through the prepolymer melt pump and the prepolymer filter. The high-viscosity final polymerization reactor is a front-rear double-axis horizontal disc reactor. The reactor outlet temperature is controlled at 280-282°C, the vacuum degree is controlled at 90-110 Pa, the outlet melt dynamic viscosity is controlled at 600-620 Pa.s, and the outlet PCTG intrinsic viscosity is controlled at 0.800 (measured in a mixed solvent with a volume ratio of phenol: tetrachloroethane of 3:2). The PCTG slice indicators are shown in Table 2.

[0088] Example 2

[0089] Example 2 provides a supported germanium-based catalyst, and uses it in the polymerization of PETG or PCTG. The specific steps are basically the same as those in Example 1, except that: step 1) is not performed when preparing the catalyst, and the ethylene glycol suspension of barium sulfate with a pH value of 7.0 in step 2) is replaced by a water suspension of γ-nanoporous alumina with a pH value of 7.0, wherein the particle size of the γ-nanoporous alumina is 35 nm and the specific surface area is 240 m 2 / g. It is used for the polymerization of PETG or PCTG, and the slice indicators of the two are shown in the following Table 1-2.

[0090] Example 3

[0091] Example 3 provides a supported germanium-based catalyst, and uses it in the polymerization of PETG or PCTG. The specific steps are basically the same as those in Example 1, except that step 1) is not performed when preparing the catalyst, and the ethylene glycol suspension of barium sulfate with a pH value of 7.0 in step 2) is replaced by a water suspension of nanoporous alumina-zirconia powder with a pH value of 7.0, wherein the particle size of the nanoporous alumina-zirconia powder is 60 nm and the specific surface area is 300 m 2 / g. It is used for the polymerization of PETG or PCTG, and the slice indicators of the two are shown in the following Table 1-2.

[0092] Example 4

[0093] Example 4 provides a supported germanium-based catalyst, and uses it in the polymerization of PETG or PCTG. The specific steps are basically the same as those in Example 1, except that step 1) is not performed when preparing the catalyst, and the ethylene glycol suspension of barium sulfate with a pH value of 7.0 in step 2) is replaced by an aqueous suspension of nanoporous silica with a pH value of 7.0, wherein the particle size of the nanoporous silica is 45 nm and the specific surface area is 270 m 2 / g. It is used for the polymerization of PETG or PCTG, and the slice indicators of the two are shown in the following Table 1-2.

[0094] Example 5

[0095] Example 5 provides a supported titanium-germanium based catalyst, and uses it in the polymerization of PETG or PCTG. The specific steps are basically the same as those in Example 1, except that: a titanium source and a germanium source are added simultaneously in step 3) when preparing the catalyst. Step 3) is as follows: the carrier containing the supported deposition layer obtained in step 2) is added with distilled water under stirring conditions to prepare a suspension with a mass percentage of 20%. After grinding the suspension twice with an ultrafine grinder, the suspension is heated to 90°C. A certain amount of dilute hydrochloric acid solution of germanium tetrachloride and a certain amount of tetrabutyl titanate are slowly added dropwise to the above suspension under stirring conditions within 4.0 hours. Germanium tetrachloride reacts with water to generate germanium dioxide, and tetrabutyl titanate reacts with water to generate titanium dioxide. Both are deposited on the surface of the supported deposition layer. During the addition process, sodium hydroxide is used to adjust the pH of the suspension so that the pH is maintained between 10.0 and 10.2. After the addition is completed, the suspension is stirred and aged for 1.5 hours at 90°C, and then a certain amount of silicate is slowly added to the suspension within 2.0 hours. After the addition is completed, the suspension is aged for 1.0 hours to obtain a catalyst suspension. The ratio of the mass of silicate to the total mass of germanium tetrachloride and tetrabutyl titanate is 1:0.2. The molar ratio of tetrabutyl titanate to germanium tetrachloride is 1:1.5.

[0096] The specific surface area of ​​the catalyst powder obtained in step 4) is 280 m 2 / g, and the particle size is 100nm. In the catalyst powder, the mass ratio of the carrier, the load deposition layer, the effective germanium in the active component, and the effective titanium in the active component is 78.1:7.5:2.5:1.25. The EG catalyst suspension obtained in step 4) is a stable suspension and can be stored for 5 months without sedimentation.

[0097] It is used for the polymerization of PETG or PCTG, and the polymerization steps are basically the same as in Example 1, except that: the esterification catalyst is replaced by tetrabutyl titanate, and its mass accounts for 3ppm (in terms of titanium element) of the total mass of the melt; the polymerization catalyst is replaced by the supported titanium-germanium composite catalyst in Example 5, wherein the mass of titanium accounts for 22.5ppm (in terms of titanium dioxide) of the total mass of the melt, and the mass of germanium accounts for 45ppm (in terms of germanium dioxide). The slice indicators of the two are shown in Tables 1-2 below.

[0098] Example 6

[0099] Example 6 provides a supported titanium-germanium-based catalyst, and uses it in the polymerization of PETG or PCTG. The specific steps are basically the same as those in Example 5, except that: step 1) is not performed when preparing the catalyst, and the ethylene glycol suspension of barium sulfate with a pH value of 7.0 in step 2) is replaced by a water suspension of γ-nanoporous alumina with a pH value of 7.0, wherein the particle size of the γ-nanoporous alumina is 35 nm and the specific surface area is 240 m 2 / g. It is used for the polymerization of PETG or PCTG, and the slice indicators of the two are shown in the following Table 1-2.

[0100] Example 7

[0101] Example 7 provides a supported titanium-germanium-based catalyst, and uses it in the polymerization of PETG or PCTG. The specific steps are basically the same as those in Example 5, except that: step 1) is not performed when preparing the catalyst, and the ethylene glycol suspension of barium sulfate with a pH value of 7.0 in step 2) is replaced by a water suspension of nanoporous alumina-zirconia powder with a pH value of 7.0, wherein the particle size of the nanoporous alumina-zirconia powder is 60 nm and the specific surface area is 300 m 2 / g. It is used for the polymerization of PETG or PCTG, and the slice indicators of the two are shown in the following Table 1-2.

[0102] Example 8

[0103] Example 8 provides a supported titanium-germanium-based catalyst, and uses it in the polymerization of PETG or PCTG. The specific steps are basically the same as those in Example 5, except that: step 1) is not performed when preparing the catalyst, and the ethylene glycol suspension of barium sulfate with a pH value of 7.0 in step 2) is replaced by an aqueous suspension of nanoporous silica with a pH value of 7.0, wherein the particle size of the nanoporous silica is 45 nm and the specific surface area is 270 m 2 / g. It is used for the polymerization of PETG or PCTG, and the slice indicators of the two are shown in the following Table 1-2.

[0104] Example 9

[0105] Example 9 provides a supported germanium-based catalyst, and the specific steps are basically the same as those of Example 1, except that: when preparing the catalyst, drying and crushing are not required in step 4), and the catalyst is directly prepared into a suspension. Step 4) is as follows: the suspension of the catalyst is filtered, washed with distilled water, and then the washed solid is dispersed in ethylene glycol to obtain a suspension, in which the mass percentage of the catalyst powder is 20%.

[0106] When it is used for the polymerization of PETG or PCTG, the polymerization effect is comparable to that of Example 1.

[0107] Comparative Example 1

[0108] Comparative Example 1 provides a polymerization method for PETG or PCTG, and its polymerization steps are basically the same as those in Example 1, except that: both the esterification and polymerization catalysts are replaced with germanium dioxide aqueous solution, and the amount of catalyst used is increased. The germanium dioxide aqueous solution is prepared by the following method: germanium dioxide powder is added to distilled water, and a reflux reaction is carried out for 8 to 10 hours, so that germanium dioxide reacts with water to form germanic acid. The mass concentration of germanium dioxide is 0.8%. The esterification catalyst accounts for 15ppm (in terms of germanium dioxide) of the total mass of the melt, and the polymerization catalyst accounts for 120ppm (in terms of germanium dioxide) of the total mass of the melt. The polymerization results are shown in Table 1-2 below.

[0109] Comparative Example 2

[0110] Comparative Example 2 provides a polymerization method for PETG or PCTG, and its polymerization steps are basically the same as those in Example 1, except that: the esterification and polymerization catalysts are both replaced with a solution of germanium dioxide water / EG mixed solvent, and the amount of catalyst used is increased. The solution of germanium dioxide water / EG mixed solvent is prepared by the following method: germanium dioxide powder is added to distilled water, heated, EG is added thereto under stirring, the mass ratio of water to EG is 1:1, and stirring and dissolving is continued to obtain a solution of a mixed solvent. In the solution, the mass concentration of germanium dioxide is 0.8%. The esterification catalyst accounts for 15ppm (in terms of germanium dioxide) of the total mass of the melt, and the polymerization catalyst accounts for 120ppm (in terms of germanium dioxide) of the total mass of the melt. The polymerization results are shown in Table 1-2 below.

[0111] Comparative Example 3

[0112] Comparative Example 3 provides a polymerization method of PETG or PCTG, and the polymerization steps are basically the same as those in Example 1, except for the types of esterification and polymerization catalysts (titanium-antimony composite catalyst), the timing of addition and the amount thereof, and the polymerization process parameters. The details are as follows:

[0113] PETG polymerization:

[0114] Continuous polymerization is carried out on a 30,000 tons / year PETG continuous polymerization device, which includes an esterification kettle, a second esterification kettle (three-chamber structure), a prepolymerization kettle, a second prepolymerization kettle, and a high-viscosity final polymerization kettle.

[0115] First, the purified terephthalic acid (PTA), ethylene glycol (EG) and molten 1,4-cyclohexanedimethanol (CHDM) were accurately measured for slurry preparation at a molar ratio of PTA:EG:CHDM = 1:0.93:0.32 and a total molar ratio of PTA:(EG+CHDM) = 1:1.25. Titanium-based catalyst tetrabutyl titanate was injected into the slurry delivery pipeline as an esterification catalyst, accounting for 3ppm (in terms of titanium element) of the total mass of the melt. The prepared slurry was then conveyed through a screw The metering pump is used to transport the liquid to the esterification kettle 1, and the temperature in the esterification kettle 1 is controlled at 254-255°C. The pressure of the process tower is 70-80kpa (positive pressure). The esterification kettle 2 is a multi-chamber design with three sub-chambers, which is convenient for adding various additives. Ethylene glycol antimony is added to the third chamber of the esterification kettle 2 as a polymerization catalyst. The polymerization catalyst accounts for 225ppm (in terms of antimony element) of the total mass of the melt. Toner and stabilizer (phosphate ester, etc.) are added to the third chamber of the esterification kettle. The esterification kettle 2 is a normal pressure reactor, and the esterification temperatures of the three sub-chambers are respectively The control is: 255-256℃ in the first chamber, 253-254℃ in the second chamber, and 257-258℃ in the third chamber; the esterified materials after the esterification reaction are introduced into the first prepolymerization kettle, which is a vertical stirring structure with inner and outer chamber designs. The reaction temperature of the first prepolymerization kettle is controlled at 262-263℃ and the vacuum degree is 9.0Kpa. The oligomers after polymerization in the first prepolymerization kettle are introduced into the second prepolymerization kettle, which is a single-axis horizontal disc reactor. The reaction temperature of the second prepolymerization kettle is controlled at 264-265℃. The prepolymer after the reaction is introduced into the high viscosity final polymerization kettle through the prepolymer melt pump and the prepolymer filter. The high viscosity final polymerization kettle is a front and rear double-axis horizontal disc reactor. The reactor outlet temperature is controlled at 275-277°C, the vacuum degree is 90-110 Pa, the outlet melt dynamic viscosity is controlled at 635-650 Pa.s, and the outlet PETG intrinsic viscosity is controlled at 0.780 (measured in a mixed solvent with a volume ratio of phenol: tetrachloroethane of 3:2). The PETG slice indicators are shown in Table 1.

[0116] Or PCTG polymerization:

[0117] Continuous polymerization is carried out on a 30,000 ton / year PCTG continuous polymerization unit, which includes an esterification kettle, a second esterification kettle (three-chamber structure), a prepolymerization kettle, a second prepolymerization kettle, and a high-viscosity final polymerization kettle.

[0118] First, the purified terephthalic acid (PTA), ethylene glycol (EG) and molten 1,4-cyclohexanedimethanol (CHDM) were accurately measured for slurry preparation at a molar ratio of PTA:EG:CHDM = 1:0.63:0.63, and a total molar ratio of PTA:(EG+CHDM) = 1:1.26. Titanium-based catalyst tetrabutyl titanate was injected into the slurry delivery pipeline as an esterification catalyst, accounting for 3ppm (in terms of titanium element) of the total mass of the melt. The prepared slurry was then conveyed through a screw The metering pump is used to transport the liquid to the first esterification kettle, and the temperature in the first esterification kettle is controlled at 256-257°C. The pressure of the process tower is 70-80kpa (positive pressure). The second esterification kettle is a multi-chamber design with three sub-chambers, which is convenient for adding various additives. Ethylene glycol antimony is added to the third chamber of the second esterification kettle as a polymerization catalyst. The polymerization catalyst accounts for 240ppm (in terms of antimony element) of the total mass of the melt. Toner and stabilizer (phosphate ester, etc.) are added to the third chamber of the esterification kettle. The second esterification kettle is a normal pressure reactor, and the esterification temperatures of the three sub-chambers are respectively The control is: 255-256℃ in the first chamber, 253-254℃ in the second chamber, and 260-262℃ in the third chamber; the esterified materials after the esterification reaction are introduced into the first prepolymerization kettle, which is a vertical stirring structure with inner and outer chamber designs. The reaction temperature of the first prepolymerization kettle is controlled at 266-268℃ and the vacuum degree is 9.0Kpa. The oligomers after polymerization in the first prepolymerization kettle are introduced into the second prepolymerization kettle, which is a single-axis horizontal disc reactor. The reaction temperature of the second prepolymerization kettle is controlled at 272-274℃. The prepolymer after the reaction is introduced into the high viscosity final polymerization kettle through the prepolymer melt pump and the prepolymer filter. The high viscosity final polymerization kettle is a front and rear double-axis horizontal disc reactor. The reactor outlet temperature is controlled at 280-282°C, the vacuum degree is 90-110 Pa, the outlet melt dynamic viscosity is controlled at 600-620 Pa.s, and the outlet PCTG intrinsic viscosity is controlled at 0.806 (measured in a mixed solvent with a volume ratio of phenol: tetrachloroethane of 3:2). The PCTG slice indicators are shown in Table 2.

[0119] Comparative Example 4

[0120] Comparative Example 4 provides a polymerization method of PETG or PCTG, and the polymerization steps are basically the same as those in Example 1, except for the types of esterification and polymerization catalysts (titanium catalysts), the timing of addition and the amount thereof, and the polymerization process parameters. The details are as follows:

[0121] PETG polymerization:

[0122] Continuous polymerization is carried out on a 30,000 tons / year PETG continuous polymerization device, which includes an esterification kettle, a second esterification kettle (three-chamber structure), a prepolymerization kettle, a second prepolymerization kettle, and a high-viscosity final polymerization kettle.

[0123] First, the purified terephthalic acid (PTA), ethylene glycol (EG) and molten 1,4-cyclohexanedimethanol (CHDM) were accurately measured for slurry preparation at a molar ratio of PTA:EG:CHDM = 1:0.93:0.32 and a total molar ratio of PTA:(EG+CHDM) = 1:1.25. Titanium-based catalyst tetrabutyl titanate was injected into the slurry delivery pipeline as an esterification catalyst, accounting for 3ppm (in terms of titanium element) of the total mass of the melt. The prepared slurry was then fed through a screw meter. The liquid is pumped to the first esterification kettle, and the temperature in the first esterification kettle is controlled at 254-255°C. The pressure of the process tower is 70-80kpa (positive pressure). The second esterification kettle is a multi-chamber design with three sub-chambers, which is convenient for adding various additives. Titanium catalyst tetrabutyl titanate is added to the third chamber of the second esterification kettle as a polymerization catalyst. The polymerization catalyst accounts for 20ppm (in terms of titanium element) of the total mass of the melt. Toner and stabilizer (phosphate ester, etc.) are added to the third chamber of the esterification kettle. The second esterification kettle is a normal pressure reactor with three sub-chambers. The temperature is controlled as follows: 255-256°C in the first chamber, 253-254°C in the second chamber, and 257-258°C in the third chamber; the esterified materials after the esterification reaction are introduced into the first prepolymerization kettle, which is a vertical stirring structure with inner and outer chamber designs, and the reaction temperature of the first prepolymerization kettle is controlled at 260-261°C and the vacuum degree is 9.0Kpa; the oligomers after polymerization in the first prepolymerization kettle are introduced into the second prepolymerization kettle, which is a single-axis horizontal disc reactor, and the reaction temperature of the second prepolymerization kettle is controlled at 261-262°C. The prepolymer after the two-reactor reaction is introduced into the high-viscosity final polymerization reactor through the prepolymer melt pump and the prepolymer filter. The high-viscosity final polymerization reactor is a front and rear double-axis horizontal disc reactor. The reactor outlet temperature is controlled at 265-267°C, the vacuum degree is 90-110 Pa, the outlet melt dynamic viscosity is controlled at 630-650 Pa.s, and the outlet PETG intrinsic viscosity is controlled at 0.780 (measured in a mixed solvent with a volume ratio of phenol: tetrachloroethane of 3:2). The PETG slice indicators are shown in Table 1 below.

[0124] Or PCTG polymerization:

[0125] Continuous polymerization is carried out on a 30,000 ton / year PCTG continuous polymerization unit, which includes an esterification kettle, a second esterification kettle (three-chamber structure), a prepolymerization kettle, a second prepolymerization kettle, and a high-viscosity final polymerization kettle.

[0126] First, the purified terephthalic acid (PTA), ethylene glycol (EG) and molten 1,4-cyclohexanedimethanol (CHDM) were accurately measured for slurry preparation at a molar ratio of PTA:EG:CHDM = 1:0.63:0.63, and a total molar ratio of PTA:(EG+CHDM) = 1:1.26. Titanium-based catalyst tetrabutyl titanate was injected into the slurry delivery pipeline as an esterification catalyst, accounting for 5ppm (in terms of titanium element) of the total mass of the melt. The prepared slurry was delivered by a screw metering pump. To the esterification kettle, control the temperature in the esterification kettle at 256-257°C, the process tower pressure: 70-80kpa (positive pressure), the esterification kettle is a multi-chamber design with three sub-chambers, which is convenient for adding various additives, add titanium catalyst tetrabutyl titanate in the third chamber of the esterification kettle, as a polymerization catalyst (the addition of the second chamber is conducive to evaporating the water in the catalyst), the polymerization catalyst accounts for 20ppm (in terms of titanium element) of the total mass of the melt, add toner and stabilizer (phosphate ester, etc.) in the third chamber of the esterification kettle, and the esterification kettle is a normal pressure reaction The esterification temperatures of the three chambers are controlled as follows: 255-256°C for chamber 1, 253-254°C for chamber 2, and 260-262°C for chamber 3; the esterified materials after the esterification reaction are introduced into the first prepolymerization kettle, which is a vertical stirring structure with inner and outer chamber designs, and the reaction temperature of the first prepolymerization kettle is controlled at 266-268°C, and the vacuum degree is 9.0Kpa; the oligomers polymerized in the first prepolymerization kettle are introduced into the second prepolymerization kettle, which is a single-axis horizontal disc reactor, and the reaction temperature of the second prepolymerization kettle is controlled at 271-273 ℃, the prepolymer after the reaction in the second prepolymerization kettle is introduced into the high viscosity final polymerization kettle through the prepolymer melt pump and the prepolymer filter. The high viscosity final polymerization kettle is a front and rear double-axis horizontal disc reactor. The reactor outlet temperature is controlled at 277-278℃, the vacuum degree is 90-110Pa, the outlet melt dynamic viscosity is controlled at 610-630Pa.s, and the outlet PCTG intrinsic viscosity is controlled at 0.800 (measured in a mixed solvent with a volume ratio of phenol:tetrachloroethane of 3:2). The PCTG slice indicators are shown in Table 2.

[0127] The polyester melt obtained in each embodiment and comparative example was sliced, and various properties of the slices were tested using the GB / T 14190-2017 standard. The results are shown in Tables 1-2 below, where IV refers to the intrinsic viscosity, which is measured in a mixed solvent of phenol and tetrachloroethane in a volume ratio of 3:2, and DEG, H2O, ash, Fe, and agglomerated particles refer to the mass fraction contents of diethylene glycol, water, ash, Fe element, and agglomerated particles in the polyester, respectively.

[0128] Table 1 PETG physical and chemical indicators

[0129]

[0130]

[0131] Table 2 Physical and chemical indicators of PCTG

[0132]

[0133] It can be seen that when the specific supported germanium-based catalyst of the present invention is used to catalyze the polymerization of PETG or PCTG, the obtained copolyester product has high viscosity and excellent hue, which is better than the traditional germanium dioxide catalyst, titanium catalyst or titanium-antimony composite catalyst. The catalyst of the present invention has higher catalytic activity and better catalytic efficiency. When achieving the same catalytic efficiency, the amount of the traditional germanium catalyst can be reduced, thereby reducing the catalyst cost.

[0134] The above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with the technology to understand the content of the present invention and implement it accordingly, and they cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a supported catalyst, wherein the supported catalyst is a surface-deposited supported germanium-based catalyst, characterized in that: The catalyst comprises a carrier, a load deposition layer and an active component, wherein the carrier is an inorganic porous material coated and modified by silicate, the load deposition layer is located on the carrier and has a porous structure, and the active component is deposited on the load deposition layer. The preparation method comprises the following steps: subjecting a suspension of the carrier, a water-soluble calcium salt, a water-soluble aluminum salt, a water-soluble zirconium salt, a water-soluble hydroxide and a base to precipitation reaction, filtering and heating to form the load deposition layer on the carrier; the base is selected from carbonate and / or bicarbonate; the specific surface area of ​​the carrier containing the load deposition layer is greater than the specific surface area of ​​the carrier; the carrier containing the load deposition layer is dispersed in water to obtain a suspension of the carrier containing the load deposition layer; A suspension of a carrier containing a loaded deposition layer is subjected to a hydrolysis reaction with a germanium source to obtain a catalyst precursor; the catalyst precursor is reacted with a silicate and water to load an active component on the loaded deposition layer to obtain the surface-deposited loaded germanium-based catalyst; the water-soluble hydroxide is selected from one or two of sodium hydroxide and potassium hydroxide; the molar ratio of the water-soluble calcium salt, the water-soluble aluminum salt and the water-soluble zirconium salt for preparing the carrier-loaded deposition layer is 0.5-2.5:1.0-2.0:0.8-3.5; in the surface-deposited loaded germanium-based catalyst, the mass ratio of the effective germanium in the carrier, the loaded deposition layer and the active component is 72.5-87.5:7.5-12.5:5.0-15.

0.

2. A method for preparing a supported catalyst, wherein the supported catalyst is a surface-deposited supported titanium-germanium based catalyst, characterized in that: The catalyst comprises a carrier, a load deposition layer and an active component, wherein the carrier is an inorganic porous material coated and modified by silicate, the load deposition layer is located on the carrier and has a porous structure, and the active component is deposited on the load deposition layer. The preparation method comprises the following steps: subjecting a suspension of the carrier, a water-soluble calcium salt, a water-soluble aluminum salt, a water-soluble zirconium salt, a water-soluble hydroxide and a base to precipitation reaction, filtering and calcining to form the load deposition layer on the carrier; the base is selected from carbonate and / or bicarbonate; the specific surface area of ​​the carrier containing the load deposition layer is greater than the specific surface area of ​​the carrier; the carrier containing the load deposition layer is dispersed in water to obtain a suspension of the carrier containing the load deposition layer; the carrier containing the load deposition layer is The suspension is subjected to a hydrolysis reaction with a germanium source and a titanium source to obtain a catalyst precursor; the catalyst precursor is reacted with a silicate and water, and an active component is loaded on the load deposition layer to obtain the surface-deposited loaded titanium-germanium-based catalyst; the water-soluble hydroxide is selected from one or two of sodium hydroxide and potassium hydroxide; the molar ratio of the water-soluble calcium salt, the water-soluble aluminum salt, and the water-soluble zirconium salt used to prepare the carrier-loaded deposition layer is 0.5~2.5:1.0~2.0:0.8~3.5; in the surface-deposited loaded titanium-germanium-based catalyst, the mass ratio of the carrier, the load deposition layer, and the effective germanium to the effective titanium in the active component is 78.1~89.4:7.5~12.5:2.5~7.5:0.6~1.

9.

3. The method for preparing a supported catalyst according to claim 1 or 2, characterized in that: The inorganic porous material is selected from one or more of nanoporous alumina, nanoporous alumina-zirconia, nanoporous silica and nanoporous barium sulfate, and has a particle size of 20-80 nm and a specific surface area of ​​220-400 m 2 / g.

4. The method for preparing a supported catalyst according to claim 3, wherein: The inorganic porous material has a particle size of 25-60 nm and a specific surface area of ​​230-320 m 2 / g.

5. The method for preparing a supported catalyst according to claim 3, wherein: The particle size of the inorganic porous material is 30-45 nm.

6. The method for preparing a supported catalyst according to claim 1 or 2, characterized in that: The water-soluble calcium salt, water-soluble aluminum salt and water-soluble zirconium salt used to prepare the carrier-loaded deposition layer are respectively selected from sulfates, acetates or chlorides of corresponding metal elements; and / or the carbonate is selected from a combination of one or more of sodium carbonate, potassium carbonate and ammonium carbonate.

7. The method for preparing a supported catalyst according to claim 1 or 2, characterized in that: The bicarbonate is selected from one or more combinations of sodium bicarbonate, potassium bicarbonate and ammonium bicarbonate.

8. The method for preparing a supported catalyst according to claim 1 or 2, characterized in that: The water-soluble calcium salt, water-soluble aluminum salt and water-soluble zirconium salt are added dropwise to the carrier suspension in the form of aqueous solution; the water-soluble hydroxide and alkali are added dropwise to the carrier suspension in the form of aqueous solution; and the preparation method controls the simultaneous addition of the two.

9. The method for preparing a supported catalyst according to claim 1 or 2, characterized in that: The molar concentration of the water-soluble calcium salt in the aqueous solution is 0.1-3.0 mol / L; and / or, the molar concentration of the water-soluble aluminum salt in the aqueous solution is 0.5-2.5 mol / L; and / or, the molar concentration of the water-soluble zirconium salt in the aqueous solution is 0.1-3.5 mol / L; and / or, the total molar concentration of the water-soluble hydroxide and alkali in their aqueous solution is 0.1-2.0 mol / L.

10. The method for preparing a supported catalyst according to claim 1 or 2, characterized in that: When forming the loaded deposition layer on the carrier, the precipitation reaction is carried out at a pH of 10-12; and / or, the precipitation reaction time is 8-11 hours; and / or, the precipitation reaction temperature is 70-100°C.

11. The method for preparing a supported catalyst according to claim 1 or 2, characterized in that: The preparation method also includes the steps of continuing to stir the suspension for 1.0-4 hours after the precipitation reaction is completed, then pressurizing to 0.7-1.2Mpa, stirring and heating to 180-200°C, balancing for 2-4 hours, then controlling the rapid decompression to normal pressure, cooling the suspension to room temperature, filtering, washing, drying and crushing.

12. The method for preparing a supported catalyst according to claim 1 or 2, characterized in that: When the load deposition layer is formed on the carrier, the temperature of the heating treatment is 290-310° C.; and / or the time of the heating treatment is 2-6 hours, the load deposition layer is further dehydrated and made porous, and the specific surface area of ​​the carrier powder containing the load deposition layer after treatment is 600-900m 2 / g, and the powder particle size is 20~50nm, and a large number of nanopores are formed on the powder surface.

13. The method for preparing a supported catalyst according to claim 11, characterized in that: The carrier powder containing the load deposition layer is mixed with water under stirring to form a suspension with a mass concentration of 10%-20%, and then ground by an ultrafine grinder for 2-3 times, and the ground suspension is heated to 60-90°C; a certain amount of germanium tetrachloride or tetraethyl germanium is slowly added to the suspension within 4.0-6.0 hours, and the germanium tetrachloride or tetraethyl germanium reacts with water under stirring to hydrolyze into germanium dioxide and deposit on the surface of the load deposition layer, and after the dropwise addition is completed, the stirring and aging are continued at 80-90°C for 1.5-2.0 hours, and then a certain amount of silicate is slowly dropped within 2.0-4.0 hours for surface coating, and after the dropwise addition is completed, the aging is continued for 1.0-3.0 hours to complete the preparation of the surface-deposited load-type germanium-based catalyst, and then filtered, washed, dried, and crushed to prepare the surface-deposited load-type germanium-based catalyst.

14. The method for preparing a supported catalyst according to claim 1, characterized in that: The germanium source is selected from one or both of germanium tetrachloride and tetraethylgermanium.

15. The method for preparing a supported catalyst according to claim 1, characterized in that: The germanium source is added dropwise to the suspension of the carrier containing the loaded deposition layer to carry out a hydrolysis reaction; and / or the mass ratio of the silicate to the germanium source is 1:0.2-0.

5.

16. The method for preparing a supported catalyst according to claim 1, characterized in that: The silicate is selected from tetraethyl silicate, tetrabutyl silicate, tetrapropyl silicate or a combination of one or more thereof.

17. The method for preparing a supported catalyst according to claim 15, characterized in that: The preparation method also includes preparing a suspension with a mass concentration of 10%-20% by weight of the surface-deposited supported germanium-based catalyst in ethylene glycol under stirring conditions, stirring evenly, and then grinding and filtering to prepare a catalyst suspension, wherein the effective germanium element content of the catalyst suspension is 1.0%-3.0% calculated as germanium dioxide.

18. The method for preparing a supported catalyst according to claim 2, characterized in that: The carrier powder containing the load deposition layer is mixed with distilled water under stirring conditions to prepare a suspension with a mass concentration of 10%-20%, and then ground by an ultrafine grinder for 2-3 times, and the ground suspension is heated to 60-90° C.; under stirring conditions, a certain amount of hydrochloric acid solution of germanium tetrachloride or tetraethyl germanium and tetrabutyl titanate or isopropyl titanate are simultaneously added dropwise to the suspension within 6.0-8.0 hours, and a sodium hydroxide-sodium bicarbonate solution is simultaneously added dropwise, and the pH value of the system is maintained between 10 and 12 during the dropping process, and the suspension is further added dropwise. A hydrolysis co-precipitation reaction is carried out to deposit the titanium source and the germanium source on the surface of the nanoporous supported deposition layer at the same time. After the dropwise addition is completed, the mixture is aged for 1.0 to 2.0 hours under stirring conditions. A certain amount of silicate is then slowly dropped into the mixed solution to adjust the pH value of the system to between 9 and 10. After the dropwise addition is completed, the mixture is aged for 1.0 to 3.0 hours to coat the surface of the nano-supported catalyst. The suspension is then filtered, and the filter cake is washed with water, and the washing is repeated until the chloride ions are completely removed. The filter cake is dried and crushed to prepare a surface-deposited supported titanium-germanium-based catalyst.

19. The method for preparing a supported catalyst according to claim 2, characterized in that: The germanium source is selected from one or both of germanium tetrachloride and tetraethyl germanium; and / or, the titanium source is selected from a combination of one or more of tetraisopropyl titanate, tetrabutyl titanate and titanium tetrachloride; and / or, the silicate is selected from a combination of one or more of tetraethyl silicate, tetrabutyl silicate and tetrapropyl silicate.

20. The method for preparing a supported catalyst according to claim 2, characterized in that: A hydrochloric acid solution of a germanium source and a titanium source are added dropwise to the suspension of the carrier containing the loaded deposition layer to carry out a hydrolysis reaction; and / or the ratio of the mass of the silicate to the total mass of the germanium source and the titanium source is 1:0.2-0.

5.

21. The method for preparing a supported catalyst according to claim 2, characterized in that: The molar ratio of titanium element to germanium element in the active component is 1:1.5-4.

5.

22. The method for preparing a supported catalyst according to claim 21, characterized in that: The preparation method also includes preparing a surface-deposited supported titanium-germanium-based catalyst into a suspension with a mass concentration of 10%-20% in ethylene glycol under stirring conditions, stirring evenly, and then grinding and filtering to prepare a catalyst suspension, wherein the catalyst suspension has an effective germanium element content of 0.5%-1.5% and an effective titanium element content of 0.12%-0.38%.

23. The method for preparing a supported catalyst according to claim 1 or 2, characterized in that: The particle size of the supported germanium-based catalyst and the titanium-germanium-based composite catalyst is 60-150 nm; and the specific surface area is 100-280 m 2 / g, and the particle size is between nanometers and sub-nanometers.

24. The supported catalyst prepared by the method for preparing a supported catalyst according to any one of claims 1 to 23.

25. Use of the supported catalyst according to claim 24 for catalyzing polyester synthesis.

26. The use according to claim 25, characterized in that: During polyester synthesis, the supported catalyst is used alone or together with a titanium-based catalyst.

27. The use according to claim 25, characterized in that: The polyester is selected from PETG or PCTG.

Citation Information

Cited By

  • Efficient PETG polymerization catalyst system and reaction regulation method, device and system thereof

    CN120699242A